1999
DOI: 10.1097/00004728-199901000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Squamous Cell Carcinoma of the Oral Cavity and Oropharynx: A Comparison of MRI and CT in T- and N-Staging

Abstract: For T-staging, MR scanning is overall more accurate than CT. If degraded images and T1 tumours are excluded, the techniques are comparable. MR scanning is oversensitive for recurrent disease. For N-staging, all methods failed to detect small metastatic deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 11 publications
2
33
0
9
Order By: Relevance
“…Recently published comparative studies on CT vs MRI for T-staging of neck primaries showed both techniques to be generally comparable [6,7]. Although not part of this study, it is noted that improvements of spiral CT technique (such as general attempts to achieve an optimum tumor contrast) may particularly improve the accuracy of CT for a more favorable comparison with novel MRI techniques.…”
Section: General Aspectsmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently published comparative studies on CT vs MRI for T-staging of neck primaries showed both techniques to be generally comparable [6,7]. Although not part of this study, it is noted that improvements of spiral CT technique (such as general attempts to achieve an optimum tumor contrast) may particularly improve the accuracy of CT for a more favorable comparison with novel MRI techniques.…”
Section: General Aspectsmentioning
confidence: 81%
“…3 The CT scans of a T3-supraglottic carcinoma (arrowhead) a 34 s, b 64 s, and c 88 s after the start of the injection of intravenous contrast material. Note the contrast performance between the tumor boundary and the right thyrohyoid muscle, and that the contrast is better at 64 and 88 s rather than at 34 s eter and/or an exact diagnosis of all infiltrated (sub-)regions [5,6,7,8,9]. Moreover, they do not take account of the increasing importance of exact volume determinations of such primaries for the prognosis and for therapy control after surgery, radiation, and/or chemotherapy [10,11,12,13,14].…”
Section: General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As MRI is superior to CT in terms of accuracy in tumor border delineation and is less susceptible to beam hardening artifacts by dental implants (12)(13)(14), many institutions prefer MRI over CT for imaging the head and neck. By combining functional and morphologic imaging, PET/CT is able to increase the sensitivity compared with morphologic imaging alone and has therefore been included in the latest guidelines for head and neck cancer imaging (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Having no threshold dose, the magnitude depends both on the volume of salivary tissue irradiated and dose of radiation delivered. Xerostomia and its associated symptoms have a considerable, negative global impact, resulting in shame, anxiety, disappointments and verbal communication difficulties [1][2][3]. Treatment of radiation induced xerostomia calls for good hydration, optimal oral hygiene and prophylaxis of candidiasis.…”
Section: Discussionmentioning
confidence: 99%